Effect of subinhibitory exposure to quaternary ammonium compounds on the ciprofloxacin susceptibility of Escherichia coli strains in animal husbandry - H. Maertens; K. Demeyere; K. De Reu; J. Dewulf; D. Vanhauteghem; E. Van Coillie; E. Meyer (BMC Microbiology, 2020)
Abstract Background Quaternary ammonium compound based disinfectants are commonly used in pig and poultry husbandry to maintain farm hygiene. However, studies have shown that subinhibitory concentrations of these disinfectants may increase antibiotic resistance. Investigation of antibiotic susceptibility is usually assessed via the microbroth dilution method, although this conventional culture-based technique only provides information on the bacteriostatic activity of an antimicrobial agent. Therefore, experiments were performed to investigate the effect of prior benzalkonium chloride (BKC) exposure on the viability of subsequent ciprofloxacin (CIP) treated Escherichia coli. Results Following CIP treatment, bacterial cell counts were significantly higher after exposure to a subinhibitory BKC concentration than without BKC exposure. The flow cytometric results suggested a BKC-dependent onset of membrane damage and loss of membrane potential. Conclusion Our results indicate a lower bactericidal effect of CIP treatment on BKC-exposed E. coli isolates compared to unexposed E. coli isolates.